Developing Culturally-Relevant Counseling In Indonesia - Sutarimah Ampuni (Faculty of Psychology Universitas Gadjah Mada, 2005)
Psychology as a science emerged in Indonesia in the 1950s. The firstpsychological work in Indonesian history was conducted by the BalaiPsychotechnik (Psychotechnik Board), a board found by the Ministry of Education, Teaching and Culture at that time. The works of the Board included conducting psychological testing for students who were going to further education, as well as performing assessments in organizations to select their prospective employees. The Boardwas later developed into the Faculty of Psychology of The University of Indonesia, the oldest psychological institution in Indonesia. In 1959, the professional organization of psychologists was founded in Jakarta (Universitas Indonesia, 2004). The second oldest educational institution of psychology, which is the Faculty of Psychology of Gadjah Mada University, was developed from the former Facultyof Educational Science in the university in 1965 (Universitas Gadjah Mada, 2004). This history implies that psychology in Indonesia was born in the context of educational science.